Clinical psychopharmacology : principles and practice - Ghaemi, S. Nassir ([New York] : Oxford University Press, 2019)
'Clinical Psychopharmacology' offers a comprehensive guide to clinical practice that explores the science and art of clinical research and its individualized application. Content is primarily based on clinical research and pharmacological studies, unlike most texts that rely on inferences from biological mechanisms. The text consists of 49 chapters, organized into 6 sections, focusing on disease-modifying versus symptomatic effects of available treatments, careful differential diagnosis including non-DSM diagnostic concepts, key clinical research studies, essential facts about the most common drugs, and more.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 4, 2019).
Keywords: Psychopharmacology